PERENCANAAN SUMBER DAYA MANUSIA YANG EFEKTIF - Soliha, Euis (Fokus Ekonomi, 2006)
Human resource planning as the process by which management determines how the organization should move from its current manpower-position to its desired position. Undoubtedly, there are many factors that account for the increased attention directed to human resource planning, but environmental forces, globalization, new technologies, economic conditions, and a changing work force seem particularly potent.  Activities related to the phases of human resource planning are described for three different time horizons: short term (up to one year), intermediate term (two to three  years), and long term (more than three years). The human resource planning process includes the following components: enviromental scan; workforce analysis; identification of significant HR issues and actions to address the issues; measuring and reporting. Keywords: Human Resource, Planning, Process.